INFLUENCES OF HEART DISEASE ON ORAL HEALTH - Iulian Constantin; Patru Radu Stanciu; Alina Mihaela Elisei; Dragos Stanciu; Cristian Guțu; Diana Oita; Alexandru Andrei Iliescu; Norina Consuela Forna; Anca Maria Fratila (Romanian Society of Oral Rehabilitation, 2024)
This review aims to explore and highlight the relationships between heart disease and oral health, highlighting the interconnections between oral health and overall heart condition. In light of recent research, it is becoming increasingly apparent that poor oral health, including conditions such as gingivitis and periodontitis, can contribute to the development or worsening of heart disease. This review looks at the biological mechanisms by which oral health problems can influence cardiovascular health, including aspects such as systemic inflammation and the dissemination of oral bacteria into the bloodstream. Prevention and management strategies for improving oral health in the context of heart disease are also discussed, highlighting the essential role of collaboration between dentists and cardiologists.